Campaign for the Brain. Issue 2 (April 2017) - Marshall, Jolene
Abstract : ABSTRACT: A stroke alert is an emergency. An event in the brain can end in long-term deficits that may be prevented if attention is given to the signs. The message needs to be told. Be fast. This is a poem to promote code stroke.